High Imminent Vertebral Fracture Risk in Subjects With COPD With a Prevalent or Incident Vertebral Fracture - van Dort, Mayke J; Geusens, Piet; Driessen, Johanna HM; Romme, Elisabeth APM; Smeenk, Frank WJM; Wouters, Emiel FM; van den Bergh, Joop PW (Journal of bone and mineral research, 2018)
ABSTRACT Subjects with chronic obstructive pulmonary disease (COPD) have an increased risk of vertebral fractures (VFs); however, VF incidence is largely unknown. Therefore, the aim of our study was to determine the incidence of new and/or worsening VF in subjects with COPD. Smokers and subjects with COPD (GOLD II–IV) from the ECLIPSE study with complete set of chest CT scans (baseline and 1‐ and 3‐year follow‐up) to evaluate vertebrae T1 down to L1 were included. If a VF was diagnosed on the last scan, detailed VF assessment of the previous scans was performed. VFs were scored according to the method of Genant as mild, moderate, or severe. Main outcome measure was the cumulative incidence of new and/or worsening VF at subject level, within 1 and 3 years. Of 1239 subjects (mean age 61 years, 757 males [61%], 999 subjects with COPD), 253 (20.5%) had ≥1 prevalent VF. The cumulative incidence of VFs was 10.1% within 1 year and 24.0% within 3 years. After adjustment for age, sex, body mass index (BMI), pack‐years, and smoking status, prevalence and incidence were similar between smokers and COPD GOLD stages. Within 1 year, 29.2% of the subjects with a prevalent VF had an incident VF, compared with 5.1% in absence of prevalent VF (hazard ratio [HR] = 5.1; 95% confidence interval [CI] 3.6–7.4) and 58.5% versus 15.0% within 3 years (HR = 3.6; 95% CI 2.9–4.6). The incidence of VF was higher with increasing number and severity of prevalent VFs. Among subjects having an incident VF within the first year, 57.3% had a subsequent VF within the next 2 years. In this study, more than half of the smokers and subjects with COPD with a prevalent VF or an incident VF within the first year sustained a subsequent VF within 3 years. The 3‐year risk was even higher in the presence of multiple or severe prevalent VFs. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.